Definition of a minimal optimal cytotoxic T-cell epitope within the hepatitis B virus nucleocapsid protein. - Bertoletti, A (1993)
Residues 11 to 27 of the hepatitis B virus nucleocapsid antigen contain a cytotoxic T-cell epitope that is recognized by cytotoxic T cells from virtually all HLA-A2-positive patients with acute hepatitis B virus infection. Using panels of truncated and overlapping peptides, we now show that the optimal amino acid sequence recognized by cytotoxic T cells is a 10-mer (residues 18 to 27) containing the predicted peptide-binding motif for HLA-A2 and that this peptide can stimulate cytotoxic T cells able to recognize endogenously synthesized hepatitis B core antigen. Since patients with chronic hepatitis B virus infection fail to mount an efficient cytotoxic T-cell response to it, this epitope might serve as the starting point for the design of synthetic peptide-based immunotherapeutic strategies to terminate persistent viral infection.